P029: Requesting prescriptions in the emergency department: the patient, the request and the response. (May 2020) - Shepherd, L.; Mucciaccio, M.; VanAarsen, K.
Abstract : Introduction: Patients presenting to the Emergency Department (ED) for the sole purpose of requesting prescriptions are problematic. Problematic for the patient, who may have a long wait to be seen and may leave dissatisfied. Problematic for the ED physician, who is in the business of episodic not comprehensive care and is diligently trying to avoid the misappropriation of medications. The primary objective of this study was to determine the characteristics of patients who present to the ED or Urgent Care Centre (UCC) requesting a prescription, the nature of these requests and the resulting action by the attending physician. The secondary objective was to determine the proportion of medication requests and responses that have potential street value. With this knowledge we may be better positioned to serve these patients and support physician decision-making. Methods: This was a single-centre, retrospective electronic chart review looking at all adult patients with a presenting complaint of medication request who attended a two-site tertiary ED or an Urgent Care Centre (UCC) in London, Ontario between April 1, 2014 and June 30, 2017. Data was tested for normality and analyzed using descriptive statistics. Results: A total of 1923 cases met the inclusion criteria. Cases were removed (n = 421) if it was unclear which prescription was requested or if a non-medication prescription or injection was requested. The patient median (IQR) age was 44 (32-54) with 58% being male and 55% having a family doctor. There were a total of 2261 prescriptions requested by 1502 patients. The top 3 most commonly requested classes of medications were opioids 433/1502 (28.8%), antidepressants/antipsychotics 371/1502 (24.7%) and benzodiazepines 252/1502 (16.8%). The median (IQR) wait time was 73 minutes (35-128). 298/1502 (19.8%) of patients received their requested prescription (opioids 12.7%; antidepressant/antipsychotic 55.3% and benzodiazepines 16.3%). 740/1502 (49.3%) of patients requested a medication that had street value. Of those, 118/740 (15.9%) received the requested medication. Conclusion: There is no "one size fits all" solution for the patient who presents to the ED requesting a prescription. The large number of requests for psychiatric medications suggests a service gap for mental health patients in the community. This data supports the need for comprehensive electronic medication records to guide physicians' decisions.